A comparison of vitamin and folic acid levels of sun and microwave dried Capsicum annuum L. Issue 6 (2nd March 2017) - Karatas, F.; Baysar, A.; Alpaslan, M.
Abstract: High Performance Liquid Chromatography was utilized to determine vitamins A, E and C, β‐carotene and folic acid levels of sun and microwave dried red pepper species ( Capsicum annuum L .). Various forms (i.e., chopped, powdered, salted and oiled) of red peppers were tested for the above mentioned vitamins, β‐carotene and folic acid levels. The results obtained in this study showed that the vitamins A and E content of sun and microwave dried samples were significantly different at p < .05 level. Vitamin C, β‐carotene and folic acid levels of red pepper species were more sensitive to the method of drying. Vitamin C, β‐carotene and folic acid levels of sun and microwave dried samples were significantly different at p < .005 level. All microwave dried samples were found to have retained higher levels of vitamins A, E and C, β‐carotene and folic acid compared to sun dried samples. Since microwave drying is fast, requires less drying time, hygienic and more vitamins are retained in the final product, it seems that microwave drying may be preferred to traditional sun drying. Practical applications: High Performance Liquid Chromatography was utilized to determine vitamins A, E and C, β‐carotene and folic acid levels of sun and microwave dried red pepper species ( Capsicum annuum L.). Various forms (i.e., chopped, powdered, salted and oiled) of red peppers were tested for the above mentioned vitamins, β‐carotene and folic acid levels. The results obtained in this study showed that the vitamins A and E content of sun and microwave dried samples were significantly different at p < .05 level. Vitamin C, β‐carotene and folic acid levels of red pepper species were more sensitive to the method of drying. Vitamin C, β‐carotene and folic acid levels of sun and microwave dried samples were significantly different at p < .005 level. All microwave dried samples were found to have retained higher levels of vitamins A, E and C, β‐carotene and folic acid compared to sun dried samples. Since microwave drying is fast, requires less drying time, hygienic and more vitamins are retained in the final product, it seems that microwave drying may be preferred to traditional sun drying.